(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This abstract provides a concise overview of the topic of fluorinated phosphates, exploring their synthesis, properties, and diverse applications across various fields. Fluorinated phosphates, characterized by the incorporation of fluorine atoms into phosphate compounds, have garnered significant interest due to their unique chemical and physical properties. This abstract summarizes key aspects of the research on fluorinated phosphates, shedding light on their synthesis methodologies, structural characteristics, and applications in areas such as materials science, catalysis, and medicinal chemistry. The study emphasizes the growing importance of fluorinated phosphates in advancing scientific and technological innovations.